PENGARUH MINAT BELAJAR DAN EFIKASI DIRI TERHADAP HASIL BELAJAR EKONOMI SMA NEGERI 2 PONTIANAK - Jeremias Eko Dewantoro; Sulistyarini Sulistyarini; Rum Rosyid (Universitas Tanjungpura, 2020)
Abstract This study aims to determine whether there is an influence of learning interest and self-efficacy on students learning outcomes in Economics subjects for class XII IPS in SMA Negeri 2 Pontianak. The research method used was descriptive in the form of interrelationship studies. The approach used in this study is quantitative. The population in this study comprised 157 students of class XII IPS. The data source was 62 students taken using a random sampling technique, and the data obtained were in the form of questionnaire answer sheets and the results of general test scores in Economic subjects in 2019/2020. The findings show that there is a significant influence between the independent variables (X1) and (X2) on the dependent variable Y. Based on the analysis, the t-test data of learning interest variables show t count 2.698 > t table 2,000 which concludes that there is an influence of learning interest on learning outcomes. The t-test data of the self-efficacy variable shows t count 2,250 > t table 2,000 which means that there is an effect of self-efficacy on learning outcomes. Meanwhile, the F-test carried out together showed an F count of 24.126> F table 3.153 which concludes that there is an influence of learning interest and self-efficacy on student learning outcomes. Keywords: Learning Interest, Learning Outcomes, Self-Efficacy